Suicidality Among Canadian University Student-Athletes - Philip Sullivan; Quinten Carfagnini; Burgandy Thiessen (Journal of Clinical Sport Psychology, 2025)
Suicide is the second most common cause of death among student-athletes. It has been consistently found that the prevalence of suicidal ideation among student-athletes is similar to, or lower than, nonathletes. However, these studies have focused on the American intercollegiate sport system, which limits the generalizability of results to different contexts. The current study examined the prevalence of suicidality of Canadian student-athletes relative to nonathletes. Varsity athletes ( n = 348) and nonathletes ( n = 9,504) participated in the 2022 Canadian cohort of the American Collegiate Health Association’s National College Health Assessment, which included the revised Suicide Behavior Questionnaire. Student-athletes’ scores on the revised Suicide Behavior Questionnaire were significantly lower than nonathletes, indicating significantly lower suicidality. Stress in the past month was a significant predictor for student-athletes, but not nonathletes. These results are largely consistent with the results from American samples.